Annotation of cis-regulatory-associated histone modifications in the genomes of two Thoroughbred stallions - Barber, Alexa M.; Kingsley, Nicole B.; Peng, Sichong; Giulotto, Elena; Bellone, Rebecca R.; Finno, Carrie J.; Kalbfleisch, Ted; Petersen, Jessica L. (Frontiers in Genetics, 2025)
The Functional Annotation of Animal Genomes (FAANG) consortium aims to annotate animal genomes across species, and work in the horse has substantially contributed to that goal. As part of this initiative, chromatin immunoprecipitation with sequencing (ChIP-seq) was performed to identify histone modifications corresponding to enhancers (H3K4me1), promoters (H3K4me3), activators (H3K27ac), and repressors (H3K27me3) in eight tissues from two Thoroughbred stallions: adipose, parietal cortex, heart, lamina, liver, lung, skeletal muscle, and testis. The average genome coverage of peaks identified by MACS2 for H3K4me1, H3K4me3, and H3K27ac was 6.2%, 2.2%, and 4.1%, respectively. Peaks were called for H3K27me3, a broad mark, using both MACS2 and SICERpy, with MACS2 identifying a greater average number of peaks (158K; 10.4% genome coverage) than SICERpy (32K; 24.3% genome coverage). Tissue-unique peaks were identified with BEDTools, and 1%–47% of peaks were unique to a tissue for a given histone modification. However, correlations among usable reads, total peak number, and unique peak number ranged from 0.01 to 0.92, indicating additional data collection is necessary to parse technical from true biological differences. These publicly available data expand a growing resource available for identifying regulatory regions within the equine genome, and they serve as a reference for genome regulation across healthy tissues of the adult Thoroughbred stallion.